Kemampuan Mahasiswa PGSD Universitas Palangka Raya dalam Mengembangkan Cerita Anak Bergambar sebagai Alternatif Media Pembelajaran Bahasa Indonesia - Widya Permata Dilla (FKIP Universitas Palangka Raya, 2024)
Elementary school age, ranging from 7-12 years, according to Piaget's development theory, is in the concrete operational phase. This phase is the initial stage where a person is able to develop the ability to think logically about an object that is concrete or real. At this phase, children who are at elementary school age are not yet fully able to understand abstract concepts. It is necessary to have the help of teaching aids/learning media to help connect reality and something abstract so that students can present real concepts from something abstract. For this reason, it is necessary for a prospective teacher to have the ability to develop illustrated stories as one of the media that can be used for learning Indonesian. This study was conducted to determine the ability of UPR PGSD students in developing illustrated children's stories. This study is a qualitative study with a descriptive approach. The subjects of observation were students of the PGSD Study Program Class C Class 2022. Data were obtained by conducting observations and documentation. The results of the study showed that most students already had good abilities in developing illustrated children's stories, although some improvements needed to achieve better results as seen from several indicators, such as creativity and originality, quality of language use, visuals and illustrations, structure and storyline, character development, and messages and moral values.